PROFESSIONAL INFORMATION TECHNOLOGY TEACHER CONTENT AND ESSENCE OF COMPETENCE DEVELOPMENT - Bahriddinovich, Avloqulov Jamoliddin (Journal of Higher Education and Academic Advancement, 2024)
This article describes the modern requirements for teachers of future technological education, the development of information acquisition competence as a pedagogical problem, and the motivations for its development.